Current Status of Electronic Theses and Dissertations (ETDs) initiatives in University Libraries of Sri Lanka - Rathnabahu, R.M.N.; Gamage, Ruwan (FACULTY OF SOCIAL SCIENCES, UNIVERSITY OF KELANIYA, 2018)
Electronic Theses and Dissertations (ETDs) is most important for academic research and plays an esteemed role in improving university ranking at present. The objective of this study is to find out the current status of Electronic Theses and Dissertations initiatives in university libraries of Sri Lanka. Fifteen (15) university libraries were selected as a sample for the study. A questionnaire was administered to fifteen university libraries and everyone replied. The data was again verified through telephone conversations and university website observations. According to the data analysis 73% of university libraries have initiated ETD projects while 07% was in the process of initiating. Twenty percent (20%) had not initiated an ETD project. The Open University of Sri Lanka, University of Peradeniya and the University of Moratuwa libraries were the pioneers of initiating ETD in Sri Lanka. All 73% libraries who had already implemented ETD were up-to-date. All libraries were using DSpace software to create ETD. Majority of the libraries have public online access up to abstracts level. Copyright issues, lack of professional staff and lack of proper training were considered as problems regarding ETD implementation in these libraries.
Keywords: ICT Applications; Electronic Theses and Dissertations; ETD; University Libraries; Sri Lanka